Application of Traditional Chinese Medical Science Characteristic Nursing Mode Based on Evidence-Based Medicine to Puerperal Breast Tenderness and Pain. (30th June 2022) - Liu, Jingying; Chen, Hua; Wang, Wei; Zhao, Dan
Abstract : Objective . To explore the effects of traditional Chinese medicine (TCM) characteristic nursing mode based on evidence-based medicine on parturients with breast tenderness and pain. Method . 100 parturients with postpartum breast pain treated at Taizhou First People's Hospital from January 2020 to December 2021 were selected. Among them, 51 cases received routine nursing intervention (general group, GG) and 49 cases received TCM characteristic nursing based on evidence-based medicine (comprehensive group, CG). The pain number (NRS) score, lactation effect, breastfeeding self-efficacy (BSES-SF) score, anxiety and depression, and nursing satisfaction of the two groups were compared. In addition, the pregnant women were followed up after discharge to investigate the rate of exclusive breastfeeding. Result . Three days after intervention, NRS score, SAS score, and SDS score in the CG were significantly lower than those in the GG. The level of serum prolactin and total breast lactation yield in the GG were better than those in the CG. BSES-SF score, nursing satisfaction, and exclusive breastfeeding rate in the CG were higher than those in the GG. Conclusion . Evidence-based TCM care can significantly reduce postpartum breast tenderness, increase milk production, improve exclusive breastfeeding, and help relieve emotional distress.